A Survey of Private Debt Funds - Block, Joern; Jang, Young Soo; Kaplan, Steven N; Schulze, Anna (The Review of Corporate Finance Studies, 2024)
Abstract Despite its large and increasing size in the United States and Europe, the private debt (PD) market, compared to the bank and syndicated loan markets, has been researched little. In this paper, we survey U.S. and European investors with private debt assets under management (AuM) of over $390 billion. These investors are primarily direct lending funds. We ask the general partners (GPs) how they source, select, and evaluate deals; how they think of private debt relative to bank and syndicated loan financing; how they monitor their investments; how they interact with private equity (PE) sponsors; and how they view the future of the market. Respondents provide primarily cash-flow-based loans and believe that they finance companies and leverage levels that banks would not fund. Direct lending funds target unlevered returns that appear high relative to their risk. They use leverage in their funds, but appreciably less than banks and collateralized loan obligation funds (CLOs). They use and negotiate for both financial and negative covenants to monitor their investments. The presence of PE sponsors helps them lend more and craft more effective covenants. U.S. and European funds are similar along many dimensions, but European funds rely less on PE sponsors and compete more with banks. Overall, the private debt market is both different from and shares characteristics with bank loan and syndicated loan markets. (JEL G23, G30, G32)